2005
DOI: 10.4269/ajtmh.2005.73.445
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Sylvatic and Domestic African Mosquito Species in Dengue Emergence

Abstract: Dengue virus 2 (DENV-2) strains that circulate in sylvatic habitats of Senegal and other parts of west Africa are believed to represent ancestral forms that evolved into endemic/epidemic strains that now circulate widely in urban areas of the tropics. Previous studies suggested that the evolution of the endemic/epidemic strains was mediated by adaptation to the peridomestic mosquito vectors Aedes aegypti and Ae. albopictus. We conducted experimental infections using sylvatic and peridomestic Senegalese mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 21 publications
2
90
2
1
Order By: Relevance
“…22 The DENV dissemination rates for Ae. furcifer captured in Senegal can be as high as 75%, 13 whereas those for YFV are estimated at 20%. 23 These estimates, based on experimental infections, were highly variable and depended on specific virus strain and mosquito genetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The DENV dissemination rates for Ae. furcifer captured in Senegal can be as high as 75%, 13 whereas those for YFV are estimated at 20%. 23 These estimates, based on experimental infections, were highly variable and depended on specific virus strain and mosquito genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Collection methods have been described previously. 2,3,13 Briefly, mosquitoes were collected at savanna and gallery forest sites surrounding Kedougou (12 11 W, 12 33 N) (Figure 2). The majority of mosquitoes were collected by human landing collection during the rainy season (generally June through October), with individuals collecting mosquitoes for 2 hours around dusk.…”
Section: Methodsmentioning
confidence: 99%
“…In studies directly comparing collections within Senegal, wide variation in VC was shown for both high-passage (Sylla et al, 2009) and low-passage field isolates of DENV-2 (Diallo et al, 2005(Diallo et al, , 2008. Especially, sylvatic collections from south-eastern Senegal were more refractory than other collections from throughout the country.…”
Section: Genetic Variability and Geographical Variations In Ae Aegypmentioning
confidence: 99%
“…aegypti with a viral isolate collected in proximity seems to be the most informative approach (Lambrechts et al, 2009). Diallo et al (2005Diallo et al ( , 2008 followed this process by examining the VC of Ae. aegypti from Senegal with multiple local isolates of DENV-2.…”
Section: Genetic Variability and Geographical Variations In Ae Aegypmentioning
confidence: 99%
See 1 more Smart Citation